FINANCIAL MANAGEMENT OF THE SINGLE TREASURY ACCOUNT IN THE ECONOMIC CRISIS - Е. І. Курганська (Ринкова економіка: сучасна теорія і практика управління)
The article analyzes modern financial management through the Treasury. The attention is paid to the specifics of Treasury Control and complexity of its structure and financial management system of Treasury. The basic problem in the management of budgetary resources and functioning treasury system, especially in a political crisis, are viewed. It was revealed that in the modern economic crisis the role of State Treasury System among budgetary institutions is very important, because it accumulates budgetary funds, monitors targeted use of financial resources of particular importance. It is shown that in today’s authorities the State Treasury Service faces one of the most active participants in the management of national and regional financial resources through the use of legally accepted mechanisms. Purpose of the article is to show that the introduction of the Single Treasury Account allows you to have information on the budget. The subject is the treasury system. The main goal is the analysis of financial management at the Treasury. In the capacity of the methodological bases the historical method, the system method, the logical method, the mathematical method, and method of analysis and synthesis were used. Practical value of the article is the examination of the financial, economic and treasury systems.